The Scleroderma Research Topics Survey for patients and health care professionals: A Scleroderma Patient-centered Intervention Network Project. Issue 3 (October 2019) - Tao, Lydia; Fedoruk, Claire; Turner, Kimberly A; Cumin, Julie; Carrier, Marie-Eve; Carboni-Jiménez, Andrea; Pépin, Mia R; Kwakkenbos, Linda; Thombs, Brett D; ,
Involving patients and health care professionals in research has been shown to be a useful strategy to generate program development ideas and establish research priorities. Online surveys can be used to identify patient research priorities. The Scleroderma Patient-centered Intervention Network is an international collaboration dedicated to researching problems important to people with scleroderma and developing, testing, and disseminating educational, self-management, rehabilitation, and psychological tools to support coping within the disease. The objectives of the Scleroderma Patient-centered Intervention Network Scleroderma Research Topics Survey were to (1) obtain input on online programs that Scleroderma Patient-centered Intervention Network could develop, (2) identify research topics important to members of the scleroderma community that could be addressed via the Scleroderma Patient-centered Intervention Network Cohort, and (3) identify potentially understudied groups. Eligible survey respondents included individuals with scleroderma and their caregivers, health care professionals, and patient organization representatives. Responses were evaluated separately for online programs, possible research questions, and understudied groups. In each category, thematic analysis was used to group responses into themes. A total of 125 participants (100 patients, 24 health care professionals, and 1 caregiver) completed the survey, and responses from patients and health care professionals were reported. For online programs, frequent recommendations included Interactive Platforms to facilitate communication between patients, as well as interventions targeting physical activity, and emotions and stress. Common responses for possible research questions were related to calcinosis, accessing health care, and quality of life. The most common suggestions for understudied groups were young patients, minority patients, and patients with calcinosis. Research topic suggestions provided in the survey will inform Scleroderma Patient-centered Intervention Network priorities and can be considered by other researchers.